Osteoprotegerin and cardiovascular disease - Vik, Anders (Universitetet i Tromsø, 2010)
The articles of this thesis are not available in Munin: 1. Vik A, Mathiesen EB, Noto AT, Sveinbjornsson B, Brox J and Hansen JB.: 'Serum osteoprotegerin is inversely associated with carotid plaque echogenicity in humans', Atherosclerosis (2007) 191(1):128-134. Available at http://dx.doi.org/10.1016/j.atherosclerosis.2006.03.002 2. Vik A, Mathiesen EB, Brox J, Wilsgaard T, Njølstad I, Jørgensen L and Hansen JB.: 'Relation between serum osteoprotegerin and carotid intima media thickness in a general population - The Tromsø Study', Journal of Thrombosis and Haemostasis (2010) 8: 2133-9. Available at http://dx.doi.org/10.1111/j.1538-7836.2010.03990.x 3. Vik A, Mathiesen EB, Johnsen SH, Brox J, Wilsgaard T, Njølstad I and Hansen JB.: 'Serum osteoprotegerin, sRANKL and carotid plaque formation and growth in a general population - The Tromso Study', Journal of Thrombosis and Haemostasis (2010) 8: 898-905. Available at http://dx.doi.org/10.1111/j.1538-7836.2010.03790.x 4. Vik A, Mathiesen EB, Brox J, Wilsgaard T, Njølstad I, Jørgensen L, Hansen JB.: 'Serum osteoprotegerin is a predictor for cardiovascular disease and mortality in a general population – The Tromsø Study', Journal of Thrombosis and Haemostasis (2011) 9: 638–644. Available at http://dx.doi.org/10.1111/j.1538-7836.2011.04222.x